Realities, scope, challenges, and facilitators for implementation of nurse practitioner's role in India: A review - Malar Kodi S; Suresh K. Sharma (Elsevier, 2021)
India is in dire need of an alternative to general medical practitioners to overcome a severe shortage of doctors, especially in rural and underprivileged regions. Empowering nurses through nurse practitioner (NP) role is the superlative solution to provide quality health care in primary care setting. Based on conceptions and research findings of the NP' s role, we analyzed and examined the realities, scope, and barriers for implementing the NP' s role in India and propose future strategies to create a NP cadre.